2013
DOI: 10.1111/cobi.12084
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Artificial Sand Fixing on Community Characteristics of a Rare Desert Shrub

Abstract: Eremosparton songoricum (Fabaceae) is a rare, native, clonal small shrub of the deserts of central Asia. Although human activities have greatly fragmented the distribution of E. songoricum, it occurs in areas where artificial sand fixing (AS) has been implemented. We sought to explore whether AS promotes survival and growth of E. songoricum. In the Gurbantunggut Desert of northwestern China in June 2010, we established 10 plots in an area where sand fixing occurred (5-10 years previously) and 11 plots on origi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 24 publications
0
9
1
Order By: Relevance
“…Accordingly, our tested species could obtain increasing amounts of available nutrients with the succession from bare sand to cyanobacteria crust and then to lichen and moss crusts. In addition, studies have reported that BSCs favor nutrient uptake by vascular plants and facilitate biomass accumulation in plant tissues (Harper & Belnap, ; Langhans, Storm, & Schwabe, ; Liu, Tao, Qiu, Zhang, & Zhang, ; Thiet, Doshas, & Smith, ). Our results also demonstrated that the plant height growth and aboveground biomass were much higher with the BSCs than with bare sand, especially the aboveground biomass, which was higher with the moss crusts than with the other substrates.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, our tested species could obtain increasing amounts of available nutrients with the succession from bare sand to cyanobacteria crust and then to lichen and moss crusts. In addition, studies have reported that BSCs favor nutrient uptake by vascular plants and facilitate biomass accumulation in plant tissues (Harper & Belnap, ; Langhans, Storm, & Schwabe, ; Liu, Tao, Qiu, Zhang, & Zhang, ; Thiet, Doshas, & Smith, ). Our results also demonstrated that the plant height growth and aboveground biomass were much higher with the BSCs than with bare sand, especially the aboveground biomass, which was higher with the moss crusts than with the other substrates.…”
Section: Discussionmentioning
confidence: 99%
“…Short-lived or ephemeral plants obtain certain development. Amaranthaceae is in a clearly dominant position while Brassicaceae, Asteraceae, Fabaceae, Poaceae, and so forth are common [21, 23, 24]. …”
Section: Methodsmentioning
confidence: 99%
“…Plant types with both short and long vegetative periods were evolved in this area [24] and short (ephemeral) plants included annuals, ainnuals/biennials, and biennials herb, so vegetative periods were divided into annuals (AH), annuals/biennials (ABH), biennials (BH), biennials/perennials (BPH), perennials (PH), shrubs (S), semishrubs (SS), small arbor (SA), annuals ephemerals (AE), annuals/biennials ephemerals (ABE), and biennial ephemerals (BE) (Table 1). …”
Section: Methodsmentioning
confidence: 99%
“…Desertification is a land-degradation process caused by intensification of human activities and climate change in fragile ecosystems of arid and semi-arid areas, and constitutes a major threat to the sustainability of agriculture and economic development (Zhu and Liu 1988;Lal 2000;Wang 2000). Preventive measures have been developed and successfully implemented in China, and include the use of wheat-straw, and planting of indigenous dune-adapted shrubs to curb desertification and alleviate its influence on crops, pasture, and human life (Zhang et al 2004;Li et al 2009;Liu et al 2013). Further, once a population of indigenous shrubs is established, it can accrue more resources, either actively through root uptake of soil water and nutrients, or passively by accumulating wind-blown dust and litter (Garner and Steinberger 1989;Gutie´rrez et al 1993;Burke et al 1995); this accrual creates a feedback mechanism that facilitates invasion and colonization by other plant species (Li et al 2009).…”
Section: Introductionmentioning
confidence: 99%